2020
DOI: 10.1145/3427332
|View full text |Cite
|
Sign up to set email alerts
|

Subtletee: Augmenting Posture Awareness for Beginner Golfers

Abstract: Mikołaj P. Woźniak et al. and auditory in an experiment with 20 beginner golfers. We found that providing proprioception feedback increased the users' performance on the driving range, with tactile feedback providing the most benefits. Our work provides insights on delivering feedback during physical activity that requires high precision movements. CCS Concepts: • Human-centered computing → Human computer interaction (HCI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…One of the more interesting findings from the user study was that practicing only auditory feedback reduced error rates for all three notes in the same manner that practicing with haptic feedback did. In a previous study on learning golf swing movements, auditory feedback was found to be inferior to visual and haptic feedback in terms of user experiences and learning effects [21]. Therefore, in the design phase of our system, we assumed that it would be difficult for the user to understand complex information if only auditory feedback was used.…”
Section: Feedback Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the more interesting findings from the user study was that practicing only auditory feedback reduced error rates for all three notes in the same manner that practicing with haptic feedback did. In a previous study on learning golf swing movements, auditory feedback was found to be inferior to visual and haptic feedback in terms of user experiences and learning effects [21]. Therefore, in the design phase of our system, we assumed that it would be difficult for the user to understand complex information if only auditory feedback was used.…”
Section: Feedback Methodsmentioning
confidence: 99%
“…Subtletee [21], compared the modalities of visual, auditory, and haptic feedback to determine which was more appropriate for the golf swing, and it was determined that haptic feedback was more appropriate. On the other hand, the feedback presented by Subtletee requires the user to recognize multiple channels of feedback during operation (the position and intensity of vibration, as well as changes in sound).…”
Section: Haptic Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…Works which compare modalities often do not offer clear-cut conclusions or modality choice or suggest using multiple modalities. For instance, Wozniak et al [56] reported that different modalities offered different advantages in supporting maintaining golf posture. Consequently, this work explores the modality design specific to the dynamic body positioning task involved in MTB rides to further understand how we can design feedback in HCI for sports.…”
Section: Feedback In Hci For Sportsmentioning
confidence: 99%
“…This is a pragmatic approach as based on past work in the sports area, e.g. Wozniak et al [56]. Choosing feedback modalities for sports where in-activity feedback was not explored before is a task with often divergent design alternatives, cf.…”
Section: User Surveymentioning
confidence: 99%